2021
DOI: 10.1002/ppul.25234
|View full text |Cite
|
Sign up to set email alerts
|

It is high time we standardize the interpretation of bronchodilator responsiveness in children

Abstract: It is high time we standardize the interpretation of bronchodilator responsiveness in children Dear Editor, I read with great attention the interesting paper of Berrier et al. 1 aiming at investigating the sensitivity and specificity of the shape indexes of the flow-volume loop to identify asthmatics from healthy children in comparison to "usual" spirometric data. I congratulate the authors for their captivating idea to explore the bronchodilator responsiveness (BDR) of shape indexes in the context of a lung f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Fourth, Lovine et al 1 reported that BDR was considered significant when >12% (i.e., relative change related to the initial value) or >200 mL (i.e., absolute change from the initial value), without specifying which spirometric datum/data was/were used (e.g., FEV 1 and/or FVC). Currently, there is no clear “consensus” on what constitutes a clinically significant BDR 6,7 . In children, a “clinically significant” BDR is definition‐dependent, and a 2021 mini‐review 6 has largely discussed the following three questions regarding the issue of a “clinically significant” BDR: which spirometric datum/data, expression mode(s), and threshold(s) should be used?…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, Lovine et al 1 reported that BDR was considered significant when >12% (i.e., relative change related to the initial value) or >200 mL (i.e., absolute change from the initial value), without specifying which spirometric datum/data was/were used (e.g., FEV 1 and/or FVC). Currently, there is no clear “consensus” on what constitutes a clinically significant BDR 6,7 . In children, a “clinically significant” BDR is definition‐dependent, and a 2021 mini‐review 6 has largely discussed the following three questions regarding the issue of a “clinically significant” BDR: which spirometric datum/data, expression mode(s), and threshold(s) should be used?…”
Section: Figurementioning
confidence: 99%
“…Currently, there is no clear "consensus" on what constitutes a clinically significant BDR. 6,7 In children, a "clinically significant" BDR is definitiondependent, and a 2021 mini-review 6 has largely discussed the following three questions regarding the issue of a "clinically significant" BDR: | 2187 which spirometric datum/data, expression mode(s), and threshold(s) should be used? The major limitation of the approach applied by Lovine et al 1 is that the absolute and relative changes in FEV 1 and FVC are inversely proportional to baseline spirometric data and are linked to sex and anthropometric data, such as height and age.…”
mentioning
confidence: 99%